The Association of COPD Exacerbations with New Onset Type 2 Diabetes among Medicare Patients - Joseph S. Marino; Cynthiya Ruban; Christopher M. Blanchette (Journal of Health Economics and Outcomes Research)
**Objective:** Chronic obstructive pulmonary disease (COPD) is highly prevalent in the elderly population and typically reduces overall quality of life. Exacerbations of COPD are commonly treated with corticosteroids, a class of drug known to cause insulin resistance. The objective of this study was to assess the rate of exacerbations requiring emergency room visits, hospitalizations or any medical encounter (a combination of emergency room and hospitalizations) between COPD patients who did and did not develop type 2 diabetes.